The Insurance markets' reactions to endogenic and exogenic shocks - Kuosmanen, Pyry (My University, 2024)
In this Bachelor’s thesis, the insurance markets' reaction to the endogenous and exogenous shocks are observed from a theoretical point of view and afterwards using the 2007-2008 Financial crisis and the Ukraine war as concrete examples.

Tässä kandidaatintutkielmassa tarkastellaan endogeenisten ja eksogeenisten sokkien vaikutuksia vakuutusmarkkinoihin teoreettisesta näkökulmasta hyödyntäen myös finanssikriisiä ja Ukrainan sotaa havainnollistavina esimerkkeinä.
Keywords: Vakuutusmarkkinat, endogeeninen sokki, eksogeeninen sokki, AIG, American International Group, finanssikriisi, Ukrainan sota, Insurance markets, Endogenic shocks, exogenic shocks, AIG, American International group, The Financial crisis, The Russo-Ukrainian war